A low frequency vibration energy harvester using dual Halbach array suspended in magnetic springs. (November 2015) - Salauddin, M; Halim, M A; Park, J Y
Abstract: An electromagnetic (EM) low frequency vibration energy harvester is newly developed based on dual Halbach array which is suspended in two magnetic springs. Each Halbach array concentrates the magnetic flux lines on one side of the array while suppressing the flux lines on the other side. Dual Halbach array allows the concentrated magnetic flux lines to interact with the same coil in a way where maximum flux linkage occurs. With the goal of higher power generation in low amplitude and low frequency vibrations, the magnetic structures (both the dual Halbach array and the magnetic springs) were optimized in terms of operating frequency and power density. A prototype was fabricated and tested. It is capable of delivering maximum 1.09mW average power to 44Ω optimum load at 11Hz resonant frequency and 0.5g acceleration. The prototype device offers 33.4μWcm -3 average power density which is much higher than recently reported electromagnetic energy harvesters.